LINGUISTIC-COGNITIVE SCENARIOS OF NATHALIE SARRAUTE’S ARTISTIC NARRATIVE - Mamosiuk, Olena (Studia Philologica, 2023)
The article is devoted to the study of the development of linguistic-cognitive scenarios of the artistic narrative of the New Novel period’s writer Nathalie Sarraute. Based on the material of the analysis of Nathalie Sarraute’s novels "Enfance", "Le Planétarium" was demonstrated that the chosen methods and techniques depend on the type of narrative and various characteristics of the text. It was determined that the meaning-making components of the linguistic-contextual model of the spiral, which is the basis of the linguistic-cognitive scenario of the SPIRAL narrative, are the retrospectivness and fragmentary nature of the narrative. It has been studied that Nathalie Sarraute’s artistic narratives also belong to the linguistic-cognitive scenario of the MOSAIC narrative, the compositional dominants of which are the detailing and framing of the narrative image. It was confirmed that linguistic-cognitive scenarios of the narrative provide for the interrelationship of syntactic, semantic, cognitive and semiotic levels, which format the plan of expression of the script construction of the novels. It was investigated that linguistic narrative scenarios exist if lexical, syntactic, and stylistic units form scenario schemes or structures in the text and give rise to the dynamics of the development of scenarios of artistic texts, and are also the embodiment of the author’s vision of the world, conveyed through the use of artistic means and techniques by writers in the text. Thus, the artistic texts of N. Sarraute are characterized by a non-linear cognitive-narrative scenography, which is a set of linguistic-cognitive narrative scenarios, namely a spiral and a mosaic.